Zakat Us an Instruments for Poverty and Inequality Reduction in Indonesian - Firman; Fuad Hassan (Global Scientific Publishing, 2023)
Poverty and income inequality are still the major problems faced by Indonesia. Some scholars argue that economics development in the country had created a tradeoff between economics growth and distribution. The conventional distribution approaches seems to file in overcoming these two problems. Hence, introduction of zakat mechanism is highly needed as an alternative approaches to solving the problems. This paper aims to discuss the role of zakat in reducing poverty and income inequality. The results show that: First, there is a significant gap between potential and realization of zakat in Indonesia. Second, the official zakat institution has not played the important role in fundraising of zakat, because there are still many zakat payers whichuse the unofficial zakat institution. Third, the allocation of budget to support the productive zakatis still limited because of some obstacles faced. However, the presence of zakat programs has reduced the poverty incidence and income inequality of zakat receivers.
Keywords: Zakat; Poverty; Income inequality; Productive Zakat